BERKUASA TANPA BEKAL AGAMA, STUDY KRITIK PEMIKIRAN NIETZSCHE - Fadillah, Dian Muhamad (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The thought of a philosopher named Nietzsche was influenced by the shadows of life in the past, where he was very disappointed with the Christian concept of ignoring the reality of life, the shackles of worship ceremonies to the point of ignoring the essence of life itself. directly reject life, because in the reality of human life has lust, by acknowledging the existence of God then the human will is shackled. One of Nietzsche's ambitions about life is the will to power, a superior human being according to him is the extent to which he is in power, but on the other hand he also does not believe in religion, even though religion plays a very important role in his assistance to power. So, in this paper, the author refutes Nietzsche's thoughts about his antipathy to religion, it is religion that prevents humans from committing criminal acts.